Superior temporal gyrus volume in patients with adjustment disorder - Tabara, Muhammed Fatih; Bibar, Alper; Koc, Mustafa; Gurok, Mehmet Gurkan; Mermi, Osman; Korkmaz, Sevda; Atmaca, Murad (Pergamon-Elsevier Science Ltd, 2026)
Introduction: Reduced superior temporal gyrus (STG) volume is associated with major depressive disorder (MDD) and posttraumatic stress disorder (PTSD), but this has not been explored in adjustment disorders. Since adjustment disorders have similar clinical features with MDD and PTSD, it was hypothesized that volume change would also occur in these disorders. Methods: In the study, nineteen patients with adjustment disorder and eighteen healthy controls were compared using MRI in terms of the STG and its subregions. Results: The STG volume of the patient group was found to be significantly reduced compared to controls (p < 0.001). In addition, the planum temporale and Heschl's gyrus subregions were significantly smaller in the patient group (in both cases p < 0.001). Conclusions: Smaller STG volumes were detected in patients with adjustment disorders, such as other psychosocial stress-related disorders, PTSD, and MDD. We should clearly state that our study is pioneering and that studies with large samples are needed to support our findings, including functional changes in the STG region.
Keywords: Adjustment disorder; Volumes; STG; Superior temporal gyrus